2017
DOI: 10.7554/elife.28951
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of asymmetric morphogenesis from 3D reconstructions of mouse heart looping dynamics

Abstract: How left-right patterning drives asymmetric morphogenesis is unclear. Here, we have quantified shape changes during mouse heart looping, from 3D reconstructions by HREM. In combination with cell labelling and computer simulations, we propose a novel model of heart looping. Buckling, when the cardiac tube grows between fixed poles, is modulated by the progressive breakdown of the dorsal mesocardium. We have identified sequential left-right asymmetries at the poles, which bias the buckling in opposite directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(159 citation statements)
references
References 85 publications
(128 reference statements)
3
156
0
Order By: Relevance
“…4A). These further developed into denser crescent-like structures with beating areas, leading to beating epithelial protrusions on the anterior portion of the gastruloids at around 168 h. Similar to mouse embryos (Ivanovitch et al, 2017;Le Garrec et al;Tyser et al, 2016), these phenotypes could be observed in gastruloids within 24 h, and could be aligned to progressive morphological stages of embryonic cardiac development between E7.5 and E8.5 (Fig. 4B).…”
Section: In Vitro Cardiac Development Occurs Through Establishment Ofmentioning
confidence: 60%
“…4A). These further developed into denser crescent-like structures with beating areas, leading to beating epithelial protrusions on the anterior portion of the gastruloids at around 168 h. Similar to mouse embryos (Ivanovitch et al, 2017;Le Garrec et al;Tyser et al, 2016), these phenotypes could be observed in gastruloids within 24 h, and could be aligned to progressive morphological stages of embryonic cardiac development between E7.5 and E8.5 (Fig. 4B).…”
Section: In Vitro Cardiac Development Occurs Through Establishment Ofmentioning
confidence: 60%
“…Nodal expression in the lateral plate mesoderm has been previously reported at 3-6 somite stages (Vincent et al, 2004). However, we found that somitogenesis is not synchronised with heart morphogenesis (Le Garrec et al, 2017), so we re-analysed Nodal expression within the context of heart looping stages. By RT-qPCR of the cardiac region, we found expression of Nodal at E8.5c-d ( Fig.…”
Section: Nodal Is Transiently Active Before Heart Looping At E85c-ementioning
confidence: 88%
“…From 3D (dimensions) reconstructions in the mouse embryo, we have previously characterised the spatiotemporal dynamics of heart looping, and established specific staging criteria. A model for a heart-specific random generator of asymmetry was proposed (Le Garrec et al, 2017). We showed that the heart tube grows between fixed poles, which is compatible with a buckling mechanism, able to generate random deformations.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations